Developing Pop-Up Book Teaching Media for Teaching Procedure Text at Grade 7 - Agustia, Fira; Nopita, Dewi; hanifah (Universitas Maritim Raja Ali Haji (UMRAH), 2024)
This research aims to develop a pop-up book as a teaching media for teaching procedure text at grade 7. Pop-up book is a book that when opened could display images that appeared to pique student enthusiasm in studying and direct their focus. This type of research is Research and Development based on ADDIE model which consists of Analysis, Design, Development, Implementation, And Evaluation. However, in this study the researcher only conducted research up to the Development stage. The data were obtained from English teacher interviews, curriculum analysis, and validation sheets. The results revealed that the lack of media use during the learning process and it is also known that students like visual media consisting of colorful images. The researcher developed a pop-up book media that received good responses from material experts and media experts. The validation results of the pop-up book media for procedure text material in grade 7 are valid. Pop-up book is categorized as very feasible because it gets 100% percentage on material validation, and gets 100% percentage on media validation.